Quantitative Insights and Challenges in Big Data from a Statistical Perspective - Ismail, Mohammed Nuther; Kallow, Sabah M.; Ridah, Mohammed Jasim; Abu-AlShaeer, Mahmood Jawad; Khlaponin, Yurii (Journal of Ecohumanism, 2024)
Background: In the age of exponential data development, big data has surpassed traditional data analysis paradigms, bringing unprecedented opportunities and substantial obstacles. The capacity to analyze large datasets is critical for acquiring insights and making educated decisions in various industries, including healthcare, finance, and technology. Objective: The article aims to highlight the varied potential given by big data analytics while also identifying the inherent obstacles found in statistical approaches, focusing on the implications for future research and applications. Methods: A complete review was conducted, synthesizing literature from databases such as PubMed, IEEE Xplore, and JSTOR. The study concentrated on recent advances in statistical models, machine learning algorithms, and their integration with big data platforms. Case studies of successful big data implementations and the statistical issues connected with them were reviewed to draw relevant conclusions. Results: The study concludes that big data provides increased predictive power and decision-making capabilities via sophisticated analytics. However, issues such as data heterogeneity, high dimensionality, and the requirement for scalable real-time analysis frameworks remain. Successful case studies often used adaptive algorithms capable of efficiently handling massive, complicated datasets. Conclusion: Big data can alter multiple sectors by offering deeper, actionable insights. Nonetheless, addressing the statistical problems is critical to realizing its full potential. Future research should establish robust, scalable statistical methods capable of adapting to the changing nature of big data environments.